2017
DOI: 10.1093/bja/aex088
|View full text |Cite
|
Sign up to set email alerts
|

Neural network imaging to characterize brain injury in cardiac procedures: the emerging utility of connectomics

Abstract: Cognitive dysfunction is a poorly understood but potentially devastating complication of cardiac surgery. Clinically meaningful assessment of cognitive changes after surgery is problematic because of the absence of a means to obtain reproducible, objective, and quantitative measures of the neural disturbances that cause altered brain function. By using both structural and functional connectivity magnetic resonance imaging data to construct a map of the inter-regional connections within the brain, connectomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
(73 reference statements)
0
12
0
2
Order By: Relevance
“…Subsequently, because statistical criteria and methods used to define POCD, neuropsychological test selection and assessment time have been primarily left to authors’ discretion, POCD incidence varies extensively across different studies [13,34]. Moreover, similarly designed studies report contradictory results; thus, a comparison of studies is difficult [20,35].…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, because statistical criteria and methods used to define POCD, neuropsychological test selection and assessment time have been primarily left to authors’ discretion, POCD incidence varies extensively across different studies [13,34]. Moreover, similarly designed studies report contradictory results; thus, a comparison of studies is difficult [20,35].…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…Interestingly, previous studies have reported that preoperative depression with an incidence between 25 and 30% is a more significant factor for POCD development after cardiac surgery than perioperative factors [37,38]. Therefore, to exclude the effects of depression and anxiety on the neuropsychological test results, appropriate tests must be applied [35]. Next, preoperative neurological examination is highly recommended [32].…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional magnetic resonance imaging (fMRI) holds promise in assessing structural and functional changes in the brain during the perioperative period. 12 Serum levels of brain-derived neurotrophic factor have been shown to be a biomarker for postoperative delirium in elderly patients. However, these are only surrogate outcomes and their utility will depend on the confidence we have that they are indeed associated with a meaningful neurodevelopmental outcome.…”
Section: The Role Of Clinical Trialsmentioning
confidence: 99%
“…However, several randomized studies have established that CPB does not affect the incidence of POD, and the use of CPB has no effect on the level of inflammatory markers [ 36 ]. Numerous studies have also confirmed that off-pump surgery does not reduce the incidence of POD [ 37 , 38 , 39 , 40 ]. Part of the risk factors, which contribute to the occurrence of postoperative delirium after cardiac surgery, may be modified in the real-world setting; some of them can be regulated only partially, but still, a few remain out of the reach of the clinicians ( Table 1 ).…”
Section: Delirium After Cardiac Surgery and Risk Factorsmentioning
confidence: 99%